Total Sleep Deprivation Followed by Bright Light Therapy as Rapid Relief for Depression: A Pragmatic Randomized Controlled Trial - Ioannou, Michael; Szabó, Zoltán; Widmark-Jensen, Mats; Vyrinis, Georgios; Karlsson, Christopher; Steingrimsson, Steinn (Frontiers in Psychiatry, 2021)
Background: Total sleep deprivation (TSD) combined with bright light therapy (BLT) has been suggested as a valuable add-on to standard treatment for rapid relief of depression. However, there is a lack of randomized controlled trials in real-life clinical settings. The aim of this pragmatic randomized clinical trial was to investigate the effectiveness, acceptance, and feasibility of TSD combined with BLT as add-on to standard treatment for depression in a real-life clinical setting. Methods: Thirty-three inpatients were randomly assigned to either: a) an intervention group receiving a single-night TSD followed by 6 days BLT (10.000 lux, 30 min/day) as add-on to standard treatment; or b) a control group receiving a short sleep-hygiene consultation in addition to standard treatment. The follow-up period was 1 week. Results: No statistical differences were found in response rates, reduction of depressive and insomnia symptoms, length of stay, readmission rate, and clinical improvement. Both groups reported positive experiences toward the received treatment with low drop-out rates. Conclusions: One-night TSD followed by BLT was not effective as a rapid relief for depression at 1-week follow-up; however, the treatment was feasible and well-tolerated.